Abstract CT230: STRIDE regimen of tremelimumab and durvalumab as non-operative management strategy of microsatellite instability-high (MSI-H) resectable gastric or gastroesophageal junction adenocarcinoma (GAC/GEJAC): Final results of the cohort 2 of INFINITY study by GONO GI - Alberto Giovanni Leone; Alessandra Raimondi; Paolo Manca; Sabina Murgioni; Giovanni G. Cardellino; Alessandro Bittoni; Antonia Strippoli; Maria Bencivenga; Federica Palermo; Floriana Nappo; Silvio K. Garattini; Thereasa Rich; et al. (Cancer Research, 2026)
Abstract Background: In resectable GAC/GEJAC, MSI-H is associated with improved survival and potential lack of benefit from chemotherapy. Pre-operative immune-checkpoint inhibitors (ICIs) achieve high rates of pathological response and promising disease-free and overall survival outcomes, possibly allowing for organ-sparing strategies. Cohort 2 of INFINITY study explored for the first time the potential role of non-operative management (NOM) in patients achieving clinical complete response (cCR) to ICIs. Patients and Methods: INFINITY is a multicentre, multicohort phase II trial (NCT04817826) investigating the activity and safety of a single high dose of tremelimumab plus durvalumab (STRIDE regimen: T300/D) as neoadjuvant (Cohort 1) or definitive (Cohort 2) 3-month treatment for MSI-H, mismatch repair deficient (dMMR) and EBV-negative resectable GAC/GEJAC. In Cohort 2, in case of cCR, defined as the absence of evidence of tumor by endoscopy, radiology and tissue-informed liquid biopsy (LB), patients underwent NOM with comprehensive re-assessments every 12-weeks for 2 years. The primary endpoint was 2-year cCR rate in absence of salvage gastrectomy. Secondary endpoints: progression-free survival (PFS), overall survival (OS), gastrectomy-free survival (GFS), safety, quality of life (QoL) and translational analyses, which included retrospective assessment of longitudinal tissue-free LB. Results: Overall, 18 pts were enrolled in Cohort 2. One withdrew consent and underwent surgery after 1 cycle. Among 17 evaluable patients, 13 (76%) achieved cCR and started NOM, of which 1 had a local regrowth after 4 months amenable to salvage surgery and follow up, while 4 did not reach cCR and received surgery. The overall 2-year cCR rate was 67%. At a median follow up of 27.1 months, no additional PD events were reported and no deaths occurred. Overall, 24-month PFS, OS and GFS rates were 94.1%, 100% and 70.6%, respectively. Grade≥3 immune-related adverse events occurred during treatment in 3 patients, all resolved with steroids with no impact on per-protocol treatment. No significant detriment on QoL was shown. Analysis of baseline LBs by the plasma-only Guardant360TM assay showed that 13/17 patients had detectable ctDNA, 10 of which detected the MSI-H status. Higher baseline ctDNA fraction trended toward a lower likelihood of reaching cCR (p=0.06). Analysis of longitudinal LB is ongoing. Conclusions: Combined T300/D for 3 months were safe and showed promising proof of efficacy for designing surgery-free approaches in MSI-H dMMR GAC/GEJAC patients selected for achieving cCR to treatment, supporting the current NCCN guidelines with long-term data for the first time in this disease. Citation Format: Alberto Giovanni Leone, Alessandra Raimondi, Paolo Manca, Sabina Murgioni, Giovanni G. Cardellino, Alessandro Bittoni, Antonia Strippoli, Maria Bencivenga, Federica Palermo, Floriana Nappo, Silvio K. Garattini, Thereasa Rich, Gaia Rebecchi, Roberta Fazio, Camilla Damonte, Margherita Ambrosini, Cecilia Villa, Greta Gronchi, Sara Lonardi, Filippo Pietrantonio. STRIDE regimen of tremelimumab and durvalumab as non-operative management strategy of microsatellite instability-high (MSI-H) resectable gastric or gastroesophageal junction adenocarcinoma (GAC/GEJAC): Final results of the cohort 2 of INFINITY study by GONO GI [abstract]. In: Proceedings of the American Association for Cancer Research Annual Meeting 2026; Part 2 (Late-Breaking, Clinical Trial, and Invited Abstracts); 2026 Apr 17-22; San Diego, CA. Philadelphia (PA): AACR; Cancer Res 2026;86(8_Suppl):Abstract nr CT230.